The Influence of Capital, Labor, and Raw Materials on Production Output at CV. Alphie Bag Company in Bogor City - Halid Adli; Yanda Bara Kusuma (International Journal of Economics Development Research (IJEDR), 2024)
This study delves into the influence of capital, labor, and raw materials on production output at CV. Alphie, a bag company in Bogor city. Employing quantitative methods with regression analysis, secondary data from CV. Alphie's reports were collected, encompassing production outputs from 2019 to 2022. Utilizing census sampling, 48 data points were obtained. The data underwent analysis using IBM SPSS version 25, and various tests were conducted, including assessments for classical assumptions, linear regression analysis, and determination coefficient testing. Results indicate that simultaneously, capital, labor, and raw materials exert a significant impact on production output. However, partially, only Labor has a significant influence on Production Output, while Capital and Raw materials do not. The findings contribute valuable insights into the factors influencing production output in manufacturing firms. Furthermore, the study has implications for managerial practices, offering guidance for optimizing production processes and resource allocation at CV. Alphie and similar companies.